Long-term outcomes of necrotizing pneumonia - Catalina Bover-Bauza; Borja Osona; Jose Antonio Gil; Jose Antonio Peña-Zarza; Joan Figuerola (Elsevier, 2021)
Introduction: Necrotizing pneumonia (NP) is a serious complication of community-acquired pneumonia characterised by the destruction of normal lung parenchyma. No study has evaluated the repercussions of the lung damage in the years following the episode. The aim of this study was to assess the long-term impact on lung function and respiratory symptoms in children hospitalised due to NP. Methods: We analysed outcomes in children given a diagnosis of NP between January 2003 and April 2016. We selected patients aged more than 4 years capable of undergoing a lung function test, that had been followed up for at least 2 years. The patients completed a respiratory questionnaire and underwent a lung function test. Results: We included a total of 24 patients (12 male). The median age at the time of diagnosis was 28 months, the median length of stay was 15 days, and 18 patients required pleural drainage. The mean duration of follow-up after NP was 8.75 years. During the evaluation, none of the patients exhibited asthma, cough, or exercise-induced symptoms. Three children had a second episode of pneumonia that did not require hospital admission. The spirometry results were the following (given as mean ± standard deviation): FEV1 Z-score, −0.47 ± 0.65; FVC Z-score, −0.56 ± 0.73; and FEV1/FVC Z-score, 0.19 ± 0.98. We found no evidence of obstructive pulmonary disease or restrictive patterns. Conclusions: The long-term outcomes of paediatric NP are good. However, patients exhibited mildly impaired lung function several years after the episode. We recommend follow-up of these patients due to potential impairments in lung function in adulthood. Resumen: Introducción: La neumonía necrotizante (NN) es una complicación grave de la neumonía adquirida en la comunidad caracterizada por la destrucción del parénquima pulmonar normal. Ningún estudio ha evaluado las consecuencias de este daño pulmonar en los años posteriores al episodio. El objetivo es investigar el impacto a largo plazo sobre la función pulmonar y los síntomas respiratorios en niños ingresados por NN. Métodos: Seguimiento de niños diagnosticados de NN desde enero-2003 hasta abril-2016. Se seleccionaron a los mayores de 4 años, capaces de realizar una función pulmonar, y un seguimiento durante más de 2 años. Los pacientes recibieron un cuestionario respiratorio y completaron una prueba de función pulmonar. Resultados: Se incluyeron 24 pacientes (12 hombres). La edad mediana en el momento del diagnóstico fue de 26 meses, 15 días de hospitalización y 18 pacientes necesitaron drenaje pleural. Los pacientes fueron seguidos durante un promedio de 8.75 años después de la NN. Durante la evaluación, ningún paciente tuvo asma, tos o sintomatología inducida por el ejercicio. Tres niños sufrieron una segunda neumonía, que no requirió hospitalización. Los resultados de la espirometría fueron (media ± desviación estándar): Z-score FEV1 −0.47 ± 0.65, Z-score FVC −0.56 ± 0.73, Z-score FEV1/FVC 0.19 ± 0.98. No hubo evidencia de enfermedad pulmonar obstructiva o patrones restrictivos. Conclusiones: Los resultados a largo plazo de la NN pediátrica son buenos. Sin embargo, los pacientes tienen una función pulmonar ligeramente disminuida varios años después del episodio. Es aconsejable hacer un seguimiento de estos pacientes debido a la posible disminución de la función pulmonar en edad adulta.